PENGARUH KOMPETENSI KERJA DAN PENGARAHAN TERHADAP TINGKAT PELAYANAN KARYAWAN CV. MEGA DUTA COMPUTINDO PAMEKASAN - Moh. Herman Djaja (Fakultas Ekonomi Universitas Yos Soedarso, 2021)
This study aims to determine and analyze how true the effect simultaneously or partially on job competence anda direction on service levels and determine the more dominant influence on service levels. The model used in this research is the mothed of observation, interview, questionnaires, and literature study using a likertslale with the sample collection method used is accidental sampling of 30 samples. The analysis method used is multiple linier regression method. The result showed the job competence anda direction simultaneously or partially had a partially significant effect on service levels CV. Mega Duta ComputindoPamekasan.Â The value of the coefficient of determination (R square) obtained 0,866, this suggests that the levels of service can be explained by twu independent variables, namely (Job Competence and Direction) CV. Mega Duta Computindo Pamekasan amounting 86,6% and the rest of 13,4% explained by other factors not included in this study.Keyword : Job Competence; Direction; Level of Service.